Level of Knowledge and Practice of Extented Program of Immunization Among Medical Students - Aneela Ambreen; Rifayatullah; Amina Zehra Iqbal; Mohammad Shadman; Shams Suleman (Gandhara University, 2015)
Objectives: To determine the level of knowledge& practice regarding extended program of immunization (EPI) in Pakistan among medical students. Design: A questionnaire based survey done amongst the students of a medical college of Peshawar. Methodology: A questionnaire was developed in the line with study objectives and circulated among students of third, fourth and final year of a medical college of Peshawar .Fifty students were selected from each class randomly. They were provided the assurance regarding the confidentiality of their response. Results: Total of 150 students was interviewed .All students were in age group 20-25 yrs. Males were 42.6% and female were 57.4%. Good knowledge was observed in 27.3% of students, average knowledge was observed in 56.6% while 16% had poor level of knowledge. Regarding practice 78% used to recommend immunization to other while 22% did not give any advice regarding immunization to anyone .Most of the students having good knowledge were from final year class (16%). Conclusion: Efforts towards ensuring adequate exposure to immunization education during training years are need to eliminate one of the barriers to adequate immunization in children.